Production of excited doubly heavy baryons at the super-Z factory - Juan-Juan Niu; Jing-Bo Li; Huan-Yu Bi; Hong-Hao Ma (European Physical Journal C: Particles and Fields, 2023)
Abstract In the framework of nonrelativistic QCD, the excited doubly heavy baryons are thoroughly studied via the channel $$e^{+} e^{-}→ \langle QQ^{′ }\rangle [n] → Ξ _{QQ^{′ }} +\bar{Q^{′ }} +{\bar{Q}}$$ e + e - → ⟨ Q Q ′ ⟩ [ n ] → Ξ Q Q ′ + Q ′ ¯ + Q ¯ , which takes place at the collision energy Z-pole. $$Q^{(′ )}$$ Q ( ′ ) represents b or c quark for the production of $$Ξ _{cc}$$ Ξ cc , $$Ξ _{bc}$$ Ξ bc , and $$Ξ _{bb}$$ Ξ bb , respectively. All of the intermediate diquark states $$\langle QQ'\rangle [n]$$ ⟨ Q Q ′ ⟩ [ n ] in P-wave, $$\langle cc\rangle [^{1}P_{1}]_{{\bar{3}}}$$ ⟨ c c ⟩ [ 1 P 1 ] 3 ¯ , $$\langle cc\rangle [^{3}P_{J}]_{{6}}$$ ⟨ c c ⟩ [ 3 P J ] 6 , $$\langle bc\rangle [^{1}P_{1}]_{{\bar{3}}/ {6}}$$ ⟨ b c ⟩ [ 1 P 1 ] 3 ¯ / 6 , $$\langle bc\rangle [^{3}P_{J}]_{{\bar{3}}/ {6}}$$ ⟨ b c ⟩ [ 3 P J ] 3 ¯ / 6 , $$\langle bb \rangle [^{1}P_{1}]_{{\bar{3}}}$$ ⟨ b b ⟩ [ 1 P 1 ] 3 ¯ , and $$\langle bb\rangle [^{3}P_{J}]_{{6}}$$ ⟨ b b ⟩ [ 3 P J ] 6 with $$J=0$$ J = 0 , 1, or 2, are taken into account. The cross sections and differential distributions, including the transverse momentum, rapidity, angular, and invariant mass, are discussed for the excited baryons production. We find that the contributions of $$\langle cc \rangle $$ ⟨ c c ⟩ , $$\langle bc \rangle $$ ⟨ b c ⟩ , and $$\langle bb \rangle $$ ⟨ b b ⟩ in P-wave are found to be 3.97 $$%$$ % , 5.08 $$%$$ % , and 5.89 $$%$$ % , respectively, compared to S-wave. Supposing that all excited states can decay into the ground state 100%, the total events $$N_{Ξ _{cc}}=8.48 × 10^{4-6}$$ N Ξ cc = 8.48 × 10 4 - 6 , $$N_{Ξ _{bc}}=2.26× 10^{5-7}$$ N Ξ bc = 2.26 × 10 5 - 7 , and $$N_{Ξ _{bb}}=4.12 × 10^{3-5}$$ N Ξ bb = 4.12 × 10 3 - 5 would be produced at the Super-Z Factory with a high luminosity up to $${{\mathcal {L}}} \simeq 10^{34-36}cm^{-2} s^{-1}$$ L ≃ 10 34 - 36 cm - 2 s - 1 .